China's security state philosophy, evolution, and politics - Guo, Xuezhi 1956- (Cambridge University Press, 2012)
China's Security State describes the creation, evolution, and development of Chinese security and intelligence agencies as well as their role in influencing Chinese Communist Party politics throughout the party's history. Xuezhi Guo investigates patterns of leadership politics from the vantage point of security and intelligence organization and operation by providing new evidence and offering alternative interpretations of major events throughout Chinese Communist Party history. This analysis promotes a better understanding of the CCP's mechanisms for control over both Party members and the general population. This study specifies some of the broader implications for theory and research that can help clarify the nature of Chinese politics and potential future developments in the country's security and intelligence services.